1193. Mucosal Antibody Responses to Respiratory Syncytial Virus (RSV) in Infants and Young Children. (4th December 2021) - Souverbielle, Cristina Tomatis; Ye, Fang; Mertz, Sara; Peeples, Mark E; Ramilo, Octavio; Mejias, Asuncion
Abstract: Background: The burden associated with RSV infection is substantial. Although RSV initially infects the upper respiratory tract, there is limited information of the mucosal concentrations of antibodies (Abs) directed to RSV specific proteins and whether patient's age and disease severity influence production of mucosal Abs. Methods: From 2017 to2019 we enrolled previously healthy children < 2 years of age hospitalized with RSV infection and obtained acute and convalescent (day; D30) nasopharyngeal (NP) samples to measure preF and postF specific IgG and IgA Abs by ELISA. Demographic and clinical data were collected and analyzed according to Abs responses. Results: We enrolled 77 children (median [IQR] age: 2.8 [1.5-5.2] months; 49 % females) within the first 24 hours of hospitalization. Of those 25 (33%) patients required PICU care. A significant increase in convalescent IgG preF Abs titers was detected in 62 (81%) children, while IgA preF titers significantly increased in all but one child on D30. The magnitude of the increase was 56-fold higher for preF IgA versus preF IgG (p< 0.0001). PostF IgG and IgA titers were also increased on D30 but at significant lower levels. Infants < 3 months of age compared with those >3-24 months had significantly higher baseline preF and postF IgG Abs titers (p < 0.001) but not IgA antibodies. D30 preF and post F IgG titers were higher in children > 6 months of age (p < 0.0001) but only preF titers fold change significantly correlated with age (r=0.4, p< 0.0001). These correlations were not identified with IgA preF antibodies. There were no statistical differences in antibody titers at baseline and on D30 according to breastfeeding, and disease severity as defined by the need for PICU care. Conclusion: Children hospitalized with RSV infection demonstrated significantly increased titers of mucosal preF and post F IgG and IgA specific Abs in convalescent samples. Baseline IgG Abs where higher in younger infants, which likely reflects maternally acquired antibodies. Age significantly correlated with Abs production, suggesting a more robust immune response in older children. Disclosures: Mark E. Peeples, PhD, Janssen (Research Grant or Support)Pfizer (Research Grant or Support) Octavio Ramilo, MD, Adagio (Consultant)Bill & Melinda Gates Foundation (Grant/Research Support)Janssen (Grant/Research Support)Lilly (Consultant)Merck (Consultant, Grant/Research Support)NIH (Grant/Research Support)Pfizer (Consultant)SANOFI (Board Member) Asuncion Mejias, MD, PhD, MsCS, Janssen (Grant/Research Support, Advisor or Review Panel member)Merck (Grant/Research Support, Advisor or Review Panel member)Roche (Advisor or Review Panel member)Sanofi (Advisor or Review Panel member)